Acceptability of meat tax and subsidy removal by meat-eaters: Insights from five European countries - Diana Kmeťková; Iva Zvěřinová; Milan Ščasný; Vojtěch Máca (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Governments worldwide are exploring policies aimed at promoting healthier and more sustainable dietary choices. This study examines the public acceptability of two promising yet controversial policy interventions: the introduction of a meat tax and the removal of meat subsidies. Drawing on existing literature about the impact of policies on food consumption, particularly meat, we analyze data from a multi-country survey conducted across five European countries. We employ ordered logistic models and cluster analysis to examine factors influencing respondents' support for these policies. Our findings highlight the role of value-based, diet-related and socio-demographic factors. Notably, respondents from Spain, Portugal, and the UK showed significantly greater support for these meat policies compared to Latvians and Czechs. Age emerged as a key factor, indicating an increasing likelihood of support for both policies among younger individuals. Moreover, environmental and egoistic values were associated with increased odds of support, while security concerns and hedonic values had the opposite effect. Education, employment, or income did not emerge as significant predictors. Our study underscores the complexity of public opinions toward meat policies and provides valuable insights for policymakers seeking to design effective strategies to promote healthier and more sustainable dietary behaviours in Europe.
Keywords: C34; C38; I15; O12; O13; Q56; 330; acceptability; clustering; meat policies; meat tax; meat subsidy removal; values